Characterisation of long-range horizontal performance of underwater acoustic communication - Pusey, Grant Mark (Curtin University, 2011)
Underwater acoustic communication is a rapidly progressing field of technology, largely due to recent advances in low cost and power efficient digital signal processors. Unfortunately, the unpredictable and time varying physical properties of the underwater acoustic channel reduce communication reliability over long ranges. This study sought to characterise the performance of horizontal underwater acoustic data communication in various scenarios with particular application to subsea monitoring and control systems.To fulfil the experimental needs, two custom-built high frequency ambient noise recorder and modem control units were developed to operate with commercial underwater acoustic modems. Additionally, an underwater acoustic communication simulator based on the Bellhop propagation model was developed for Matlab, capable of producing performance predictions in both spatial and temporal studies. A series of short-term trials were conducted to determine the limitations of modem performance over different ranges. These trials included shallow water studies off the coast of Perth, Western Australia (D < 30 m), and a French deep water trial (D ≤ 1000 m) which used stand-alone modems. Experimental findings were compared to predictions obtained using two-dimensional range-depth performance simulations.A long-term investigation of the environmental influences on modem reliability was carried out off the coast of Perth in approximately 100 m of water. This involved simultaneously collecting environmental and modem performance data for over 16 days. The signal to noise ratio remained high for the duration of the trial so modem performance fluctuations could be attributed to changes in channel propagation. Using multiple linear regression, the measured environmental parameters were correlated with the observed modem performance and their contributions to an overall fitting curve were calculated. It was determined that the sound speed profile, in addition to the sea surface roughness, contributed strongly to the fitting curve, with a weaker contribution from the measured signal to noise ratio. This result was confirmed by performing temporal simulations which incorporated more detailed time-dependant environmental parameters. By progressively adding more parameters to the simulator including ambient noise, wave height and the sound speed profile, simulations provided more accurate predictions of the observed performanceOverall, the horizontal performance of underwater acoustic communication was characterised in several scenarios from a series of experimental and numerical investigations. Additionally, the developed simulator was shown to be an effective and flexible tool for predicting the performance of an underwater acoustic communication system. The results and tools discussed in this thesis provide an extensive investigation into the factors influencing horizontal underwater acoustic communication. The analysis demonstrates that whilst underwater acoustic communication can be effective, it is not yet a viable alternative to cabled telemetry for long-range subsea monitoring and control applications, where reliability is crucial. Underwater acoustic communication would best be suited as a non-critical or backup method for continuous monitoring systems until channel prediction and equalisation techniques are further refined.